2018
DOI: 10.1136/neurintsurg-2018-014459
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of observational evidence for the use of bailout self-expandable stents following failed anterior circulation stroke thrombectomy

Abstract: BackgroundThe crucial role of thrombectomy in the management of emergent large vessel occlusive stroke is not disputed but there is a technical failure rate in a significant minority of patients whose outcomes are often poor. Our objective was to perform a systematic review and meta-analysis to assess the safety and efficacy of permanent self-expandable stent deployment as a bailout procedure in cases of failed anterior circulation thrombectomy.MethodsTwo independent reviewers searched the Pubmed (Medline) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…In our study on ICS for moderately severe stroke, 2/41 patients experienced sICH. This result is comparable to those in the HERMES meta-analysis with 4.4% and is unexpectedly low compared to the latest acute ICS studies that reported on sICH rates ranging from 8 to 17% (1,12). Antithrombotic medication was administered periinterventionally in all our cases, some even in combination with IVT.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study on ICS for moderately severe stroke, 2/41 patients experienced sICH. This result is comparable to those in the HERMES meta-analysis with 4.4% and is unexpectedly low compared to the latest acute ICS studies that reported on sICH rates ranging from 8 to 17% (1,12). Antithrombotic medication was administered periinterventionally in all our cases, some even in combination with IVT.…”
Section: Discussionsupporting
confidence: 82%
“…Recent retrospective case series have suggested reconsidering ICS as a bailout strategy when MT fails to recanalize LVOs (11,19). All these ICS studies report on typical thrombectomy cohorts with a median admission NIHSS ranging from 14 to 19 (12). However, there are currently no reports on ICS after failed thrombectomy for a homogenous group of less severe stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These RCTs still represent the best available evidence for ICS in patients with symptomatic intracranial stenosis. Currently, ICS achieved promising results for intracranial stenosis in the setting of acute ischemic stroke after failed mechanical thrombectomy 6 7. However, elective ICS (eICS) as an endovascular treatment option for secondary stroke prevention has remained unpopular, although recurrence rates of stroke are high in patients with symptomatic intracranial stenosis despite best medical treatment 8.…”
Section: Introductionmentioning
confidence: 99%
“…Wareham et al in their analysis reported the rate of successful recanalization as 71% and favorable outcome in 43% of the patients. 60 But the studies included were mostly retrospective and heterogenous. However, use of self-expandable stents as a bailout procedure appears to be a reasonable approach.…”
Section: Bail Out Stents Following Failed Anterior Circulation Thrombmentioning
confidence: 99%